Investigation on transverse defect and cavitation depth in ferrous pipe using melt spun FeSiB ribbon as magnetostrictive sensing element. (June 2016) - Panda, A.K.; James, Ajil P.; Mohan, Aneesh; Dey, Sushmita; Roy, R.K.; Mitra, A.
Abstract: The investigation addresses the scope of rapidly quenched Fe80 Si8 B12 ribbons as magnetostrictive sensor (MsS) material to generate guided waves in galvanised iron pipe and evaluation of defects with different geometries and dimensions. Enhancement in the effective defect size (EDS) of transverse and pit type defects increased the MsS signal. However, the backwall echo showed opposing trend (transverse: reduced and pit: increased) with increase in dimensions of these defects. Such behaviour of backwall intensities has been correlated to different type of guided wave strain field distributions around these defects and reflection coefficients.